Early sexual behaviour and Chlamydia trachomatis infection - a population based cross-sectional study on gender differences among adolescents in Norway. - Gravningen, Kirsten Midttun; Furberg, Anne-Sofie; Simonsen, Gunnar Skov; Wilsgaard, Tom (BMC Infectious Diseases, 2012)
This article is part of Kirsten M. Gravningen's doctoral thesis, available in Munin at http://hdl.handle.net/10037/5649 Early sexual behaviour has been shown to differ significantly between genders, but few studies have addressed this topic to explain the commonly observed differences in chlamydia rates between adolescent girls and boys. Our study aimed to determine chlamydia prevalence in adolescents aged 15–20 years in a high-incidence area in Norway, and to identify gender-specific early sexual behaviours associated with infection. A population based cross-sectional study was conducted among all high school students in five towns in Finnmark county in 2009, using a web-based questionnaire and real-time Chlamydia trachomatis PCR in first-void urine samples (participation rate 85%, 800 girls/818 boys, mean age 17.2 years). Crude and multivariable logistic regression models were applied with chlamydia test result as dependent variable. Prevalence of chlamydia infection was 5.7% (95% confidence interval, CI, 4.4–7.3%). Girls were twice as likely to be infected as boys (7.3%, 5.3–9.7 vs 3.9%, 2.3–6.0). Girls reported earlier sexual debut, older partners, higher lifetime number of partners, and were poorer condom users. In girls, higher maternal education (odds ratio, OR, 2.2, 95% CI 1.1–4.4), ≥2 sexual partners past 6 months (OR 3.6, 1.8–7.3), and partner meeting venue at a private party, bar or disco (OR 5.0, 1.1–22.7) increased the odds of infection in the multivariable model. In boys, condom use at first intercourse (OR 0.06, 0.01–0.42) decreased the odds of infection, while having an older last sexual partner (OR 3.7, 1.3–11.0) increased the odds. In all participants, the risk of infection increased if residence outside the family home during school year (OR 2.0, 1.2–3.6), and decreased if condom was used at last intercourse (OR 0.2, 0.1–0.8). We detected significant gender differences in chlamydia prevalence and sexual behaviours, and accordingly differing independent risk factors for chlamydia infection. ...